Near-infrared luminescent material as well as preparation method and application thereof

Through the near-infrared luminescent materials of Na3-yM2-x-z(PO4)2F3:xCr3+, yR3+, zN, combined with solid-phase synthesis method, the problem of poor thermal stability of near-infrared phosphor is solved, and efficient near-infrared light emission is achieved. in a variety of application fields.

CN119264906AActive Publication Date: 2025-01-07XIAMEN INST OF RARE EARTH MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310805685.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-07
Estimated Expiration
2043-07-03

AI Technical Summary

Technical Problem

The emission intensity of existing near-infrared phosphors decreases at high temperatures and has poor thermal stability, which affects the luminous efficiency of near-infrared LEDs.

Method used

The near-infrared luminescent material using Na3-yM2-x-z(PO4)2F3:xCr3+, yR3+, zN was prepared by solid phase synthesis method. Cr3+ is used as the luminescence center, and an appropriate amount of trivalent rare earth elements and divalent doping elements are combined to form A near-infrared luminescent material with high thermal stability can emit 650-1200 nm of near-infrared light under excitation of 350-750 nm.

Benefits of technology

It realizes the maintenance of emission intensity at high temperatures, improves the thermal stability and luminous efficiency of near-infrared LEDs, and is suitable for a variety of application fields, such as detection, marking, identification and optoelectronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264906A_ABST
    Figure CN119264906A_ABST
Patent Text Reader

Abstract

The invention discloses a near-infrared luminescent material as well as a preparation method and application thereof. The chemical formula of the near-infrared luminescent material is Na3-yM2-x-z (PO4) 2F3: xCr < 3 + >, yR < 3 + > and zN, M is a trivalent metal element, Cr < 3 + > is a luminescent central ion, R is a trivalent rare earth element, N is a divalent doping element and / or a trivalent doping element, x is selected from 0.0001 at.%-30 at.%, y is selected from 0 at.%-50 at.%, and z is selected from 0 at.%-50 at.%. The light-emitting material and a blue light or red light chip are packaged to obtain an LED device, and the LED device can be used as a near-infrared light source to be used in the fields of analysis and detection, iris recognition, automobile sensing, security and protection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of luminescent materials, and in particular relates to a near-infrared luminescent material and a preparation method and application thereof. Background Art

[0002] Near-infrared light refers to electromagnetic waves with an emission band between 700nm and 2500nm. Since Herschel discovered near-infrared radiation in 1800, it has attracted widespread attention. In recent years, researchers have conducted in-depth research on this type of radiation and developed a variety of applications that promote the advancement of modern technology, such as medical diagnosis, biological imaging, plant lighting, food and medicine, night vision security, etc. Traditional near-infrared light sources include halogen tungsten lamps, laser diodes, etc. However, specific commercial uses have put forward requirements on the size and manufacturing cost of near-infrared light sources, prompting us to develop more portable, efficient and economical near-infrared light sources. Since the invention of blue light-emitting diodes (LEDs), phosphor conversion LEDs (pc-LEDs) obtained by integrating inorganic phosphor materials with blue LED chips have brought revolutionary progress to the lighting, display and other industries. In 2016, OSRAM announced the industry's first commercial broadband near-infrared LED, which is based on this technical solution. Near-infrared broadband phosphors are coated on high-efficiency blue LED chips, and broadband near-infrared emission is achieved by exciting near-infrared phosphors with blue light.

[0003] Near-infrared light with different emission wavelengths has different applications. Red light at 730nm can be detected by plant pigment protein P FR 810nm near-infrared light is often used in biometric identification technology in mobile devices; 830nm near-infrared light is often used in automatic card swiping applications on highways because of its good night vision effect; 840nm near-infrared light is used in color zoom infrared cameras; 850-870nm infrared light has good applications in video shooting and surveillance cameras; 940nm is used in remote controls because of its strong resistance to light interference; 970nm near-infrared light is often used in food analysis because it can measure the content of moisture, protein, etc. As for longer-wavelength infrared light, it is more used in fields such as solar cells.

[0004] Although there are many types of near-infrared phosphors developed at this stage, most of them face problems such as low luminous efficiency and poor stability. Among them, near-infrared phosphors are particularly seriously affected by thermal quenching. The heat generated during the operation of the LED chip (≥150℃) will cause the emission intensity of the phosphor to decrease, which is usually attributed to the non-radiative relaxation of the excited electrons of the activated ions under high-temperature thermal activation. This thermal quenching phenomenon seriously affects the luminous efficiency of NIR-LEDs. Therefore, it is particularly important to develop a near-infrared phosphor with good thermal stability. Summary of the invention

[0005] The present invention provides a near-infrared luminescent material, the chemical formula of which is Na 3-y M 2-x-z (PO4)2F3:xCr 3+ ,yR 3+ ,zN,

[0006] Among them, M is a trivalent metal element, Cr 3+ is a luminescent central ion, R is a trivalent rare earth element, N is a divalent doping element and / or a trivalent doping element, x is selected from 0.0001 at.%-30 at.%, y is selected from 0 at.%-50 at.%, and z is selected from 0 at.%-50 at.%.

[0007] According to an embodiment of the present invention, M is selected from one, two or more of Al, V, Cr, Fe, Ga and Sc.

[0008] According to an embodiment of the present invention, R is selected from one, two or more of Eu, Pr, Sm and Er.

[0009] According to an embodiment of the present invention, N is, for example, one, two or more selected from Mg, Zn, Fe, and In.

[0010] According to an embodiment of the present invention, x is 0.0001 at.% to 10 at.%, for example, 1 at.%, 2 at.%, 3 at.% or 5 at.%.

[0011] According to an embodiment of the present invention, y is 0 at.%-5 at.%, for example, 0 at.%, 1 at.%, 2 at.%, 3 at.% or 5 at.%.

[0012] According to an embodiment of the present invention, z is 0 at.%-5 at.%, for example, 0 at.%, 1 at.%, 2 at.%, 3 at.% or 5 at.%.

[0013] According to an exemplary embodiment of the present invention, the near-infrared luminescent material is Na 3-y Al 2-x-z (PO4)2F3:xCr 3+ ,yR 3 + , zN, wherein y and z are 0, and x is 1 at.%, 3 at.% or 5 at.%.

[0014] According to an exemplary embodiment of the present invention, the near-infrared luminescent material is Na 3-y Al 2-x-z (PO4)2F3:xCr 3+ ,yR 3+ , zN, where z is 0, and x and y are both 3at.%.

[0015] According to an exemplary embodiment of the present invention, the near-infrared luminescent material is Na 3-y AlGa 1-x-z (PO4)2F3:xCr 3+ ,yR 3+ , zN, where y and z are 0, and x is 3at.%.

[0016] According to an embodiment of the present invention, the near-infrared luminescent material can emit near-infrared light with a wavelength range of 650-1200 nm after being excited by blue light or red light.

[0017] Preferably, the blue light or red light is selected from blue light or red light in the range of 350-750 nm.

[0018] Preferably, the peak value of the near infrared light is between 750-850 nm, for example, around 810 nm.

[0019] The present invention also provides a method for preparing the above-mentioned near-infrared luminescent material, which is a solid phase synthesis method, specifically comprising the following steps:

[0020] The near-infrared luminescent material is obtained by weighing raw materials according to the stoichiometric ratio of each element in the chemical formula of the near-infrared luminescent material, mixing the raw materials, and subjecting the raw materials to heat treatment and sintering treatment.

[0021] According to an embodiment of the present invention, the raw material includes a Na-containing compound, an M-containing compound, a P-containing compound, an F-containing compound, a Cr-containing compound, and at least one of the following substances: an R-containing compound, a N-containing compound.

[0022] According to an exemplary embodiment of the present invention, the raw materials include a compound containing Na, a compound containing M, a compound containing P, a compound containing F, and a compound containing Cr.

[0023] According to an embodiment of the present invention, the Na-containing compound is selected from one or both of Na2CO3 and NaF.

[0024] According to an embodiment of the present invention, the compound containing M is selected from one of oxides of M, fluorides of M, and phosphates of M, or two or more thereof.

[0025] According to an embodiment of the present invention, the P-containing compound is selected from one or two or more of NH4H2PO4, (NH4)2HPO4, and AlPO4.

[0026] According to an embodiment of the present invention, the Cr-containing compound is one or both of Cr2O3 and CrF3.

[0027] According to an embodiment of the present invention, the R-containing compound is selected from R oxides.

[0028] According to an embodiment of the present invention, the N-containing compound is selected from one or two or more of N oxides, N carbonates, and N fluorides.

[0029] According to an embodiment of the present invention, the raw materials may be pre-baked before or after mixing.

[0030] Preferably, the pre-baking treatment refers to treating the raw materials at a temperature above 150° C. (eg, 190° C., 250° C.) for a period of time (eg, 3-5 hours) and then allowing them to cool naturally to room temperature.

[0031] According to an embodiment of the present invention, the mixing method is selected from one or both of dry grinding and wet grinding. Preferably, the mixing method is wet grinding with an appropriate amount of anhydrous ethanol for 10-200 minutes, for example, at least 30 minutes or 60 minutes.

[0032] According to an embodiment of the present invention, the heat treatment includes heating, keeping warm and cooling.

[0033] According to an embodiment of the present invention, the heating refers to heating from room temperature to the insulation temperature at a heating rate of 1-5°C / min.

[0034] According to an embodiment of the present invention, the insulation conditions refer to: the insulation temperature is less than 600° C., for example, 400° C.; the insulation time is 1-5 hours, for example, 4 hours.

[0035] According to an embodiment of the present invention, the cooling refers to cooling to room temperature at a cooling rate of 1-5°C / min.

[0036] According to an embodiment of the present invention, the sintering treatment time is greater than 6 hours, for example, 10-48 hours.

[0037] According to an embodiment of the present invention, the temperature of the sintering treatment is 600-720°C, more preferably 680-700°C, for example 690°C.

[0038] According to an embodiment of the present invention, the sintering process further includes heating before the sintering process, and the sintering process further includes cooling after the sintering process, and the heating and cooling have the meanings as described above.

[0039] According to an exemplary embodiment of the present invention, the sintering treatment comprises: heating from room temperature to a sintering temperature at a heating rate of 1-5°C / min for 10-48 hours, and then cooling to room temperature at a cooling rate of 1-5°C / min.

[0040] According to an embodiment of the present invention, after sintering, grinding is optionally performed, and the near-infrared luminescent material is collected after grinding.

[0041] According to an embodiment of the present invention, after heat treatment and / or sintering treatment, grinding may be optionally performed. The grinding may be performed under conditions known in the art as long as uniform powder can be obtained, such as dry grinding in a mortar for more than 30 minutes.

[0042] According to an exemplary embodiment of the present invention, the preparation method includes the following steps:

[0043] (1) according to the stoichiometric ratio of each element in the chemical formula of the near-infrared luminescent material, weigh a Na-containing compound, an M-containing compound, a P-containing compound, a F-containing compound, a Cr-containing compound, and an optional R-containing compound and a N-containing compound, respectively, and mix them to obtain a mixed powder;

[0044] Pre-baking is optionally performed before or after mixing;

[0045] (2) The mixed powder in step (1) is subjected to heat treatment and sintering treatment to obtain the near-infrared luminescent material.

[0046] The present invention also provides the use of the above-mentioned near-infrared luminescent material, which can be used as a near-infrared luminescent material in various fields using near-infrared light sources, such as detection, marking, identification, optoelectronic equipment, etc.

[0047] According to an embodiment of the present invention, the near-infrared luminescent material of the present invention is used in LED.

[0048] The present invention also provides an LED device, comprising at least one of the near-infrared luminescent materials.

[0049] According to an embodiment of the present invention, the LED device further comprises an LED chip, and the LED chip may be a blue light LED chip or a red light LED chip, preferably a 420nm blue light chip.

[0050] According to an embodiment of the present invention, in the LED device, the near-infrared luminescent material is disposed on the surface of the LED chip.

[0051] According to an exemplary solution of the present invention, the LED device is excited by a 350-750nm blue light LED chip or a red light LED chip to obtain near-infrared light with an emission wavelength of 650-1200nm, and can be used as a near-infrared light source.

[0052] The present invention also provides the use of the LED device as a near-infrared light source in the fields of analysis and detection, iris recognition, automobile sensing and security.

[0053] Beneficial effects:

[0054] The present invention provides a near-infrared luminescent material, comprising Cr 3+ It is the luminescence center and can effectively emit 650-1200nm near-infrared light under the excitation of 350-750nm light.

[0055] The present invention adopts a solid phase method to synthesize the near-infrared luminescent material, which has the advantages of low raw material cost, simple process, easy operation, etc., and is easy to realize large-scale preparation of the luminescent material.

[0056] The near-infrared luminescent material provided by the present invention can be effectively excited by existing commercial blue light or red light LED chips, and can be packaged to obtain LED devices, thereby realizing the commercialization of near-infrared light LED devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 This is a comparison chart of the XRD of different phosphors prepared in Examples 1-5 of the present invention and the XRD calculated by COD#1521541.

[0058] Figure 2 This is an excitation spectrum diagram of the phosphor prepared in Example 2 of the present invention at a monitoring wavelength of 810 nm.

[0059] Figure 3 Comparison of emission spectra of the phosphor samples prepared in Examples 1-3 of the present invention under 426nm blue light excitation.

[0060] Figure 4 The phosphor sample prepared in Example 1 of the present invention has a temperature-varying spectrum of 25-200° C. under 426 nm blue light excitation.

[0061] Figure 5 This is the excitation spectrum of the phosphor prepared in Example 4 of the present invention obtained at a monitoring wavelength of 830 nm and the emission spectrum obtained at a monitoring wavelength of 426 nm.

[0062] Figure 6 This is a comparison chart of the emission spectra of the phosphors prepared in Example 2 and Example 5 of the present invention under 426nm blue light excitation. DETAILED DESCRIPTION

[0063] The preparation method of the present invention will be described in further detail below in conjunction with specific examples. It should be understood that the following examples are only exemplary illustrations and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0064] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0065] The monitoring wavelength in the present invention refers to selecting the emission peak position or the vicinity of the wavelength band as the monitoring wavelength to obtain an excitation spectrum with a high signal-to-noise ratio; the testing instrument is an FLS980 fluorescence spectrometer.

[0066] Example 1-5: Na 3-y M 2-x-z (PO4)2F3:xCr 3+ Preparation of luminescent materials

[0067] Examples 1-5 were synthesized by high temperature solid phase method, and only differed in the types and amounts of raw materials. For specific types and amounts of raw materials, please refer to Table 1, where the units of raw material amounts are grams.

[0068] The specific steps of high-temperature solid-phase synthesis are as follows: weigh the reaction raw materials according to the stoichiometric ratio, place them in an agate mortar and grind them thoroughly for 3-5 minutes, add an appropriate amount of alcohol to place the powder raw materials in the mortar, grind them for 30-60 minutes, and then place the above mixture in a 60-80°C oven for 5-10 minutes to dry it; after cooling to room temperature and taking it out, grind it appropriately to mix the powder stuck in the mortar again, and collect the powder in a corundum crucible after mixing; cover the crucible containing the powder and place it in a 190°C oven for 3-5 hours, let it cool naturally to room temperature, transfer the mixture to an agate mortar, and dry grind it for 10-30 minutes, collect the mixed powder in a corundum crucible, cover it, and then place it in a muffle furnace. The pre-sintering temperature is set to be raised from room temperature to 400°C at a heating rate of 1-5°C / min, kept at 400°C for 4 hours, and then cooled to room temperature at a cooling rate of 1-5°C / min; the pre-sintered powder sample is taken out, placed in an agate mortar, ground for 15-30 minutes, and then the powder sample is collected in a corundum crucible, covered and transferred to a muffle furnace for sintering, and the sintering temperature is set to be raised from room temperature to 690°C at a heating rate of 1-5°C / min, kept at 690°C for 6 hours, and then cooled to room temperature at a cooling rate of 1-5°C / min, and finally, the sintered phosphor sample is taken out, placed in a mortar, ground for 20-30 minutes, and the phosphor is collected to obtain a near-infrared luminescent material. The sample is subjected to phase analysis by an X-ray diffractometer, and the spectral characteristics of the sample are measured by an FLS980 (Edinburgh Instruments) fluorescence spectrometer.

[0069] Table 1 Preparation parameters of Examples 1-5

[0070]

[0071] The samples synthesized by the high temperature solid phase method of the present invention, XRD analysis shows that the samples of Examples 1-5 are all pure phase: Figure 1 ae are the XRD patterns of samples in Examples 1-5, which match the COD card (see Figure 1 Na3Al2(PO4)2F3).

[0072] Figure 2 This is an excitation spectrum diagram of the phosphor prepared in Example 2 of the present invention at a monitoring wavelength of 810 nm. The results show that the prepared luminescent material has a broadband excitation peak between 350-750 nm, with the best excitation positions at 426 nm and 640 nm.

[0073] Figure 3 This is a comparison chart of the emission spectra of the phosphor samples prepared in Examples 1-3 of the present invention under 426nm blue light excitation, Figure 3 The a, b and c lines represent the Cr in the chemical formula of the phosphor sample.3+ When the doping amount x is 1at.%, 3at.%, and 5at.%, the room temperature emission spectra of the samples show that compared with the samples with 1at.% and 5at.%, Cr 3+ When the doping amount is 3at.%, the emission intensity of the sample is higher.

[0074] Figure 4 The temperature spectrum of the phosphor sample prepared in Example 1 of the present invention under 426nm blue light excitation in the range of 25-200°C is as follows: Figure 4 The lines a, b and c represent the emission spectra of the phosphor sample of Example 1 at room temperature, 150°C and 200°C respectively. The results show that the luminescent material prepared by the present invention has negative thermal quenching properties in the range of room temperature to 150°C, and the emission intensity at 150°C is 100.33% of the emission intensity at room temperature; the emission intensity at 200°C can maintain 81.49% of the emission intensity at room temperature.

[0075] Figure 5 The excitation spectrum of the phosphor prepared in Example 4 of the present invention at a monitoring wavelength of 830 nm and the emission spectrum at a monitoring wavelength of 426 nm are shown. 3+ The introduction can achieve a red shift in the emission wavelength of the phosphor while leaving the excitation spectrum almost unchanged.

[0076] Figure 6 The emission spectra of the phosphors prepared in Example 2 and Example 5 of the present invention under 426nm blue light excitation are compared. The a and b lines are the emission spectra of Example 2 and 5, respectively. It can be seen that the simultaneous introduction of Ga 3+ and Eu 3+ The luminous intensity decreased slightly.

[0077] Example 6: Preparation of LED Devices

[0078] The luminescent material synthesized in Example 2 was taken, and its luminescence quantum yield PL QY was tested and recorded in Table 2.

[0079] The luminescent material synthesized in Example 2 is mixed with silica gel and then coated on a blue LED chip, wherein the mass ratio of the luminescent material to the silica gel is 1:1; then cured and packaged to obtain a near-infrared emitting LED device, which can be used as a near-infrared light source in various analytical and detection equipment. The near-infrared output power of the LED device is shown in Table 2.

[0080] Table 2 Performance test results

[0081] Luminescent Materials PL QY (%) Near infrared output power (mW) Example 2 64% 28.13

[0082] Test Case

[0083] The phosphor of Example 2 was tested for emission spectra at room temperature and 150°C, and the integral areas S1 and S2 were calculated. The integral area ratio S2 / S1 of the emission spectra at 150°C and room temperature was calculated, and the results were consistent with those of the reported ScBO3:Cr 3+ The phosphors with similar emission bands are compared and recorded in Table 3. From the results in Table 3, it can be seen that compared with the phosphors with the same band, the luminescent material of the present invention has a huge advantage in thermal stability.

[0084] Table 3 Performance comparison

[0085]

[0086] The above embodiments illustrate the implementation methods of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc. made by those skilled in the art within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A near-infrared luminescent material, the chemical formula of which is Na 3-y M 2-x-z (PO4)2F3:xCr 3+ ,yR 3 + ,zN, in, M is a trivalent metal element, Cr 3+ is a luminescent central ion, R is a trivalent rare earth element, N is a divalent doping element and / or a trivalent doping element, x is selected from 0.0001 at.%-30 at.%, y is selected from 0 at.%-50 at.%, and z is selected from 0 at.%-50 at.%.

2. The near-infrared luminescent material according to claim 1, characterized in that: M is selected from one, two or more of Al, V, Cr, Fe, Ga and Sc. Preferably, R is selected from one, two or more of Eu, Pr, Sm and Er. Preferably, N is selected from one, two or more of Mg, Zn, Fe and In.

3. The near-infrared luminescent material according to claim 1 or 2, characterized in that: x is 0.0001 at.%-10 at.%. Preferably, y is 0 at.%-5 at.%. Preferably, z is 0 at.%-5 at.%.

4. The near-infrared luminescent material according to any one of claims 1 to 3, characterized in that: After being excited by blue light or red light, the near-infrared luminescent material emits near-infrared light with a wavelength ranging from 650 to 1200 nm. Preferably, the blue light or red light is selected from blue light or red light in the range of 350-750 nm. Preferably, the peak value of the near infrared light is between 750-850 nm.

5. The method for preparing the near-infrared luminescent material according to any one of claims 1 to 4, wherein the method is a solid phase synthesis method, specifically comprising the following steps: The near-infrared luminescent material is obtained by weighing raw materials according to the stoichiometric ratio of each element in the chemical formula of the near-infrared luminescent material, mixing the raw materials, and subjecting the raw materials to heat treatment and sintering treatment.

6. The preparation method according to claim 5, characterized in that: The raw materials include a compound containing Na, a compound containing M, a compound containing P, a compound containing F, a compound containing Cr, and at least one of the following substances: a compound containing R and a compound containing N. Preferably, the Na-containing compound is selected from one or both of Na2CO3 and NaF. Preferably, the compound containing M is selected from one of oxides of M, fluorides of M, and phosphates of M, or two or more thereof. Preferably, the P-containing compound is selected from one or two or more of NH4H2PO4, (NH4)2HPO4, and AlPO4. Preferably, the Cr-containing compound is one or both of Cr2O3 and CrF3. Preferably, the R-containing compound is selected from R oxides. Preferably, the N-containing compound is selected from one or two or more of N oxides, N carbonates and N fluorides.

7. The preparation method according to claim 5 or 6, characterized in that: The mixing method is selected from one or both of dry grinding and wet grinding. Preferably, the heat treatment includes heating, keeping warm and cooling. Preferably, the heating refers to heating from room temperature to the insulation temperature at a heating rate of 1-5°C / min. Preferably, the insulation conditions are: the insulation temperature is less than 600° C.; and the insulation time is 1-5 hours. Preferably, the cooling refers to cooling to room temperature at a cooling rate of 1-5°C / min. Preferably, the sintering time is greater than 6 hours. Preferably, the sintering temperature is 600-720°C. Preferably, the sintering process further includes heating before the sintering process, and the sintering process further includes cooling after the sintering process. Preferably, the sintering treatment comprises: heating from room temperature to a sintering temperature at a heating rate of 1-5°C / min for 10-48 hours, and then cooling to room temperature at a cooling rate of 1-5°C / min. Preferably, after sintering, grinding is optionally performed, and the near-infrared luminescent material is collected after grinding.

8. Use of the near-infrared luminescent material according to any one of claims 1 to 4.

9. An LED device, comprising at least one near-infrared luminescent material according to any one of claims 1 to 4.

10. Use of the LED device according to claim 9 as a near-infrared light source in the fields of analysis and detection, iris recognition, automobile sensing and security.

Citation Information

Patent Citations

  • Ion conductor material for secondary battery and preparation method thereof

    CN109817975A

  • Near-infrared luminescent material and preparation method thereof, and LED light source containing luminescent material

    CN117736729A